أنموذجا Bard الذكاء الاصطناعي والتماسك النصي تطبيق - شاشة, شروق; دريش, غالية; حميداني, هاجر; بن عمر, وصال (University of Eloued جامعة الوادي, 2024)
تعالج مذكرتنا موضوعا علميا جديدا متمثلا في ربط المادة اللسانية بالعلوم التكنولوجية متمثلة في الذكاء الاصطناعي الذي تجاوز الجملة الى نوعية معينة من النصوص، مُشكّلا عنوان بحثنا" التماسك النصي والذكاء الاصطناعي" فأدى بنا إلى تقسيمه شقين: شق نظري، عالجنا فيه أهم تفصيلات دراستنا، وشق تطبيقي، حاولنا فيه جمع أهم التطبيقات التي تنظر في تماسك النصوص واستخراج آلياتها ووسائلها. واتبعنا في ذلك كله منهجا وصفيا، وبتحليل النتائج توصلنا إلى أن الذكاء الاصطناعي أصبح قادرا على أن يؤدي ما جاءت به لسانيات النص بالحكم على النص من اللانص Our dissertation addresses a new scientific topic, represented by linking linguistic material to technological sciences, represented by artificial intelligence, which went beyond the sentence to a specific type of text. This formed the title of our research, “Textual Cohesion and Artificial Intelligence,” which led us to divide it into two parts: a theoretical part, in which we dealt with the most important details of our study, and a practical part, we tried to collect the most important applications that look at the cohesion of texts and extract their mechanisms and means. In all of this, we followed a descriptive approach. By analyzing the results, we concluded that artificial intelligence has become able to perform what linguistics came up with in judging text from non-text.